Dysgerminoma: A Rare Case of Malignant Ovarian Tumor (Mediscope, 2025)
Background: Dysgerminoma is a germ cell tumor of the ovary, most commonly occurring in young females. Regarding behavior, it’s a malignant tumor. But early diagnosis usually leads to a good prognosis.Case summary: A 23-year-old female presented with lower abdominal pain, anorexia, weight loss, and on clinical examination palpable mass in the left lower abdomen. Ultrasound showed a large, irregular, lobulated solid mass (measuring 22×21cm) on the left ovary and mild ascites. A surgical approach was decided as the first-line treatment.  Microscopic aspects were consistent with dysgerminoma. There was no metastasis.Conclusion: Dysgerminoma usually has a favorable prognosis if diagnosed early. Histopathological confirmation and staging are necessary for further management.Mediscope 2025;12(2): 84-87